DIGITAL LEADERSHIP IN IMPROVING TEACHER PERFORMANCE DURING THE COVID-19 PANDEMIC - Pribadi, Luthfi Audia; Nurdin , Diding; Edy, Sarwo (CV. AFDIFAL MAJU BERKAH, 2024)
Education involving digital technology is the latest transformation in the education system, especially during the COVID-19 pandemic. During the current Covid-19 Pandemic, education must be carried out using online digitalization between Educators and Students as well as Education Personnel and school committees. The study aims to overcome the Leadership Model which is influenced by rapid technological developments by changing the model. This research is a qualitative research using literature study method. Research on literature studies on learning media for distance learning (online) in early childhood is important to do. The research results show Traditional Leadership towards Digital Leadership. A leader, especially a stakeholder in the education sector, needs to know the advantages and disadvantages of the digital world itself and be able to inspire his subordinates to innovate and defend ideas. Deep acumen applying digital leadership benchmarks demonstrates a fast-paced, cross-hierarchical, cooperative, and often team-oriented approach to integrating innovation. The novelty of this research is that it shows that the ability to plan and organize digital leadership programs is important and can help improve students’ academic performance, despite the COVID-19 pandemic crisis.